2018
DOI: 10.1111/padm.12413
|View full text |Cite
|
Sign up to set email alerts
|

Macro‐economic coordination and elusive ownership in the European Union

Abstract: The notion of ownership is well known in relation to global governance. In the realm of EU macro‐economic coordination, it has become a buzzword since the revamping process of the European Semester in 2015. This article investigates how ownership by four types of domestic actors (governments, administrations, parliaments and social partners) manifests itself in the European Semester. We conceptualize three types of ownership, namely institutional, political, and cognitive. Using network analysis, semi‐structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…The concept of “policy ownership” was initially elaborated in relation to the policies of international organizations. It basically means “that a policy is not only imported from an external actor to the local level, but that the local level participates in reflecting on it” (Vanheuverzwijn & Crespy, : 580). It is further assumed that if an actor comes to own a policy, this actor will be willing to take responsibility for policy choices because—possibly through an iterative process—they match his or her preferences, or because the actor finds that the procedures that led to these choices are legitimate.…”
Section: Policy Ownership and Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of “policy ownership” was initially elaborated in relation to the policies of international organizations. It basically means “that a policy is not only imported from an external actor to the local level, but that the local level participates in reflecting on it” (Vanheuverzwijn & Crespy, : 580). It is further assumed that if an actor comes to own a policy, this actor will be willing to take responsibility for policy choices because—possibly through an iterative process—they match his or her preferences, or because the actor finds that the procedures that led to these choices are legitimate.…”
Section: Policy Ownership and Learningmentioning
confidence: 99%
“…This, in turn, would lead to economic reforms that benefit all euro area members. The evidence for 2012 suggested that where the scrutiny would potentially be most useful in economic terms is where it was least practiced.” Even Vanheuverzwijn and Crespy (), who distinguish between three dimensions of ownership—the institutional capacity to shape, the political willingness to engage, and the cognitive awareness—of the European Semester and see it as a remedy for various input, output, and throughput deficits that would otherwise taint it, end up considering ownership as an oversight and control of national executives performed severally by national parliaments, by their committees and potentially also by other subjects such as subnational authorities and social partners.…”
Section: Executive Dominance Sidelining Of Representative Assembliesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Commission sees the creation of domestic ownership as a key mechanism to achieve Semester's throughput legitimacy. This paper draws on Vanheuverzwijn and Crespy (2018) to conceptualize ownership. They distinguish between institutional, political and cognitive ownership.…”
Section: The Semester and Throughout Legitimacymentioning
confidence: 99%
“…Germany's strong national fiscal position, French reservation toward the Commission's proposal for restructuring the labour market, and the dominant role of social stakeholders in wage setting in Finland are concrete examples of a tendency toward national ownership, as discussed in this paper. A discussion about ownership of a policy reform usually occurs in an international policy context with multiple actors involved (see Vanheuverzwijn and Crespy 2018;Koeberle, Bedoya, Silarsky and Verheyen 2005).…”
Section: Potential Effects On Eu Policy Coordinationmentioning
confidence: 99%